Crecimiento del guapote lagunero (Cichlasoma dovii) en regimen de cultivo intenso en estanques y su dependencia de la densidad - Günther Nonell, Jorge (Uniciencia, 1996)
Growth and feed utilization of the Dow cichlid (Cichlasoma dovii) were assessed when cultured intensively in earthen ponds at two different densities (1,4 and 2.8 fish/m2). Growth and feed utilization were superior by 20% and 13%, respectively, at the lower density. A pronounced sexual difference in mean weight was detected (final weights 317,2 and 113,9g. for males and females, respectively) and frequency distributions were used to determinate separatedly the growth of males and females .